2018
DOI: 10.1556/030.65.2018.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated quinolone resistance determinants in Enterobacteriaceae from urine clinical samples

Abstract: Plasmid-mediated quinolone resistance (PMQR) determinants including, qnrA, qnrB, qnrC, qnrD, qnrS, aac(6')-Ib-cr, oqxAB, and qepA, were investigated in 214 Enterobacteriaceae strains from urine clinical samples. Antimicrobial susceptibility testing for ciprofloxacin, ceftriaxone, and imipenem was performed by broth microdilution method. All strains were screened for PMQR genes by PCR. Virulence determinants, namely afa, pap, pil, sfa/foc, and kpsMT of eight Escherichia coli strains proven positive for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…The most prevalent PMQR gene is oqx B with more abundance in Klebsiella pneumonia strains. ( Yuan et al, 2012 ) and Szabó et al (2018) also reported the presence of oqx AB gene in all human K. pneumoniae strains investigated. However, in a recent study on Klebsiella strains isolated from broiler, qnr B was the most dominant followed by qnr S and with low prevalence of qep A and qnr A ( Wu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The most prevalent PMQR gene is oqx B with more abundance in Klebsiella pneumonia strains. ( Yuan et al, 2012 ) and Szabó et al (2018) also reported the presence of oqx AB gene in all human K. pneumoniae strains investigated. However, in a recent study on Klebsiella strains isolated from broiler, qnr B was the most dominant followed by qnr S and with low prevalence of qep A and qnr A ( Wu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 77%
“…The observed resistance may be due to an univestigated gene. Resistance of Morganella morganii to quinolones has been linked to qnr D, two new gyr B mutations (S463A, S464Y) and one par C mutation (S80I) ( Nasri et al, 2014 ; Szabó et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…qnrD gene was found in 4.5% of the isolates. Previous papers reported qnrD in bacteria isolated from rooks [ 51 ], pigs [ 15 ] and humans clinical isolates of Salmonella enterica serovar Kentucky, serovar Bovismorbificans, Proteus mirabilis and Morganella morganii [ 52 , 53 ], as well as in E. coli from dogs [ 54 ]. In accordance to others studies [ 19 , 55 , 56 ], qepA was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…In Northwest Iran, prevalence of PMQRs in Enterobacteriaceae isolated from UTIs showed a very high prevalence about 89.1% and among them aac(6′)-Ib-cr was the most frequently detected [22]. In Hungary, prevalence of PMQR-positive Enterobacteriaceae isolated from urine clinical samples showed 17.7% [23]. In the past 8 years, incidence of PMQRs among ESBL-producing E. coli and K. pneumoniae from bloodstream infection increased in Hungary [24].…”
Section: Introductionmentioning
confidence: 98%